In vivo imaging of cellular proliferation in renal cell carcinoma using 18F-fluorothymidine PET - Peter K. Wong; Sze Ting Lee; Carmel Murone; John Eng; Nathan Lawrentschuk; Salvatore U. Berlangieri; Kunthi Pathmaraj; Graeme J. O'Keefe; John Sachinidis; Amanda J. Byrne; Damien M. Bolton; Ian D. Davis; et al. (Asia Oceania Journal of Nuclear Medicine and Biology, 2014)
Objective(s): The ability to measure cellular proliferation non-invasively in renal cell carcinoma may allow prediction of tumour aggressiveness and response to therapy. The aim of this study was to evaluate the uptake of 18Ffluorothymidine (FLT) PET in renal cell carcinoma (RCC), and to compare this to 18F-fluorodeoxyglucose (FDG), and to an immunohistochemical measure of cellular proliferation (Ki-67). Methods: Twenty seven patients (16 male, 11 females; age 42-77) with newly diagnosed renal cell carcinoma suitable for resection were prospectively enrolled. All patients had preoperative FLT and FDG PET scans. Visual identification of tumour using FLT PET compared to normal kidney was facilitated by the use of a pre-operative contrast enhanced CT scan. After surgery tumour was taken for histologic analysis and immunohistochemical staining by Ki-67. Results: The SUVmax (maximum standardized uptake value) mean±SD for FLT in tumour was 2.59±1.27, compared to normal kidney (2.47±0.34). The mean SUVmax for FDG in tumour was similar to FLT (2.60±1.08). There was a significant correlation between FLT uptake and the immunohistochemical marker Ki-67 (r=0.72, P